2021
DOI: 10.2147/prbm.s309194
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impacts During the Initial Phase of the COVID-19 Outbreak, and its Associated Factors Among Pastoral Community in West Omo Zone, South-West Ethiopia, 2020: A Community-Based Study

Abstract: Background COVID-19 is a global pandemic and a major health crisis affecting several nations. Such outbreaks are associated with adverse mental health consequences to any group of the population. Despite its negative effects, no study has addressed the potential psychological impacts of the COVID-19 outbreak among the pastoral community. This study aims to assess psychological experiences during the early stages of the COVID-19 outbreak and the factors that contributed to it among pastoral communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the current study, the 19-25 and 36-45 age groups reported significant associations with depression. A published study from China confirmed that the young adult group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) suffered from mental health issues (Qiu et al, 2020). 13 A study published in Spain demonstrated a similar finding of high depression and stress in young adults 18-33 years old (Jiménez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the 19-25 and 36-45 age groups reported significant associations with depression. A published study from China confirmed that the young adult group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) suffered from mental health issues (Qiu et al, 2020). 13 A study published in Spain demonstrated a similar finding of high depression and stress in young adults 18-33 years old (Jiménez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study's cut-off scores were derived from Lovibond and Lovibond (1995). After multiplying each subscale by 2, the results were categorized as follows: depression-normal (0−9), mild (10−13), moderate (14−20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (≥28); anxiety-normal (0−7), mild (8−9), moderate (10−14), severe (15)(16)(17)(18)(19) and extremely severe (≥20); and stress-normal (0−14), mild (15−18), moderate (19−25), severe (26)(27)(28)(29)(30)(31)(32)(33) and highly severe (≥34). Summed scores of 10 and above indicated depression, eight and above marked anxiety, and 15 and above labeled it as stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation